(untitled) (Journal of Pharmaceutical Negative Results, 2022)
This article is investigating study of genitourinary system morbidity indicators in the adult population of Osh region for the period 2010-2019. Materials and methods: selection and summary information on the main indicators characterizing the morbidity among adult population in the Osh region with genitourinary system diseases for the period from 2010 to 2019 was based on statistical data. When comparing two data rows based on their mean values, the Student's t-test was used to compare values. Differences were considered as reliable at significance level p<0.05. Research results: When analysing the obtained data, it can be noted that the highest value of genitourinary system total morbidity was recordedin 2017 (46546 people per 100000 population), the lowest in 2019 (31722 people per 100000 population) (p<0.05). A similar trend was observed among women: the maximum value of the general morbidity indicator was revealed in 2017 (33496 per 100 thousand population), the minimum in 2019 (23140 per 100 thousand population). The lowest indicator of this parameter in men is in 2019 (8582 per 100 thousand population). The highest value of the indicator of primary morbidity is in 2011 was 22501 per 100 thousand. The population in 2015 was 22899 per 100000 population, the smallest as 11591 per 100 thousand population in 2019. Kidney and urinary system diseases (N00-N39)-21.05% lead among nosological primary morbidity in the general structure, among them chronic pyelonephritis (N11) has the largest specific weight during the entire observation period.